The Influence of Flash Sales and Discounts on USU Students’ Shopee Purchases - Delviana Sinaga; Miarisa Sitepu; Rumondang Tri Hany; Yesaya Simarmata; Nurmala Fitri; Erikson Saragih (Economos : Jurnal Ekonomi dan Bisnis, 2026)
The development of digital technology has transformed student consumption patterns, with Shopee becoming one of the most popular marketplaces thanks to its easy access, diverse payment methods, and aggressive promotional strategies. This study analyzes the influence of flash sales and discounts on student purchasing decisions. The method used was a quantitative survey with a questionnaire for student Shopee users, analyzed descriptively and inferentially. The results show that flash sales and discounts both have a significant influence, but their mechanisms differ. Flash sales tend to trigger impulsive decisions through urgency and FOMO, while discounts are perceived as more rational due to the financial benefits they offer. However, the emotional aspect of flash sales proved more dominant in driving purchases, even for non-priority products. These findings confirm the effectiveness of limited-time promotions in digital marketing strategies and provide critical reflection for students to be more discerning when shopping online